Sustainability of Hybrid Maize Cultivation during spring in the Hilly Region of Koraput District of Odisha - Behera, S. K.; Maharana, J.; Acharya, P. (Indian Journal of Hill Farming, 2017)
Maize (Zea mays L.) is an important cereal crop in world after rice and wheat. Maize is grown on around 2.3 lakh hectares in Orissa. Kharif maize alone accounts for about 2.2 Lakh hectares. In Koraput district, Kharif maize is cultivated around in 20,000 ha whereas Rabi Maize is cultivated in 3250 ha. Maize cultivation during the spring season was introduced by the Krishi Vigyan Kendra, Koraput during 2013-14 under the ISOPOM maize programme. The demonstration was given to 40 nos of beneficiaries covered 3 villages such as Maliburuda and Muliaput of Nandapur block and Luhaba village of Semiliguda block. The demonstration on hybrid maize (Var: JK 101) was conducted in 12 ha. The maize crop was sown during 10th to 18th January 2014 and was harvested during 20th to 25th April 2014. Only seeds and fertilizer have been supplied to the farmers for the demonstration programme. The average maize yield was found to be 46.34q/ha which is 57.8% higher yield than the control plot of local variety. The average cost of cultivation of the maize crop was Rs. 40,500 per hectare and gross return was found to be Rs. 85,500 per hectare. Average net profit of Rs. 45,000 per hectare was found by cultivating the maize in the spring season. Krishi Vigyan Kendra, Koraput is playing a vital role in disseminating the technology of cultivating the hybrid maize cultivation during spring season. It was found from the technology transfer result that highest adoption was the irrigation and water management followed by farm mechanization. Overall full adoption of the scientific technology in maize production was found to be 46.17%. Farmers expressed their satisfaction over the yield performance of the maize during spring season. The technology transferred is also profitable and acceptable to the farming community. Further research need to be focused on the problems and constraint for adoption of the technology.